Ubiquinol-cytochrome C reductase core protein II promotes tumorigenesis by facilitating p53 degradation - Han, Yingyan (EBioMedicine, 2019)
BACKGROUND: Ubiquinol-cytochrome C reductase core protein II (QCR2) is essential for mitochondrial functions, yet, its role in cancer development has remained elusive. METHODS: The expression of QCR2 in cancer patients was assessed by immunohistochemistry. The proliferation of cancer cells was assessed by CCK-8 assay, EdU staining and Flow cytometry analysis. The biological function of QCR2 and PHB were determined using western blotting, RT-qPCR, microarray analysis and xenografts. The interactions between proteins and the ubiquitination of p53 were assessed by immunoprecipitation, mass spectrometry analysis and GST pull down. The subcellular location of PHB and QCR2 was assessed by immunoblotting and immunofluorescence. FINDING: The expression of QCR2 is upregulated in multiple human tumors. Suppression of QCR2 inhibits cancer cell growth by activating p53 signaling and inducing p21-dependent cell cycle arrest and senescence. QCR2 directly interacts with PHB in the mitochondria. Overexpression of QCR2 inhibits PHB binding to p53 in the nucleus, and facilitates p53 ubiquitination and degradation, consequently leading to tumorigenesis. Also, increased QCR2 and decreased PHB protein levels are well correlated with decreased expression of p21 in cervical cancer tissues. INTERPRETATION: These results identify a novel role for QCR2, together with PHB, in negative regulation of p53 stability and activity, thus promote cervical carcinogenesis. FUND: “973” Program of China, the National Science-technology Supporting Plan Projects, the National Natural Science Foundation of China, National Science and Technology Major Sub-Project and Technical Innovation Special Project of Hubei Province.